Genome-wide identification and function analysis of the sucrose phosphate synthase MdSPS gene family in apple - Li-hua ZHANG; Ling-cheng ZHU; Yu XU; Long LÜ; Xing-guo LI; Wen-hui LI; Wan-da LIU; Feng-wang MA; Ming-jun LI; De-guo HAN (Journal of Integrative Agriculture)
Sucrose phosphate synthase (SPS) is a rate-limiting enzyme that works in conjunction with sucrose-6-phosphate phosphatase (SPP) for sucrose synthesis, and it plays an essential role in energy provisioning during growth and development in plants as well as improving fruit quality. However, studies on the systematic analysis and evolutionary pattern of the SPS gene family in apple are still lacking. In the present study, a total of seven MdSPS and four MdSPP genes were identified from the Malus domestica genome GDDH13 v1.1. The gene structures and their promoter cis-elements, protein conserved motifs, subcellular localizations, physiological functions and biochemical properties were analyzed. A chromosomal location and gene-duplication analysis demonstrated that whole-genome duplication (WGD) and segmental duplication played vital roles in MdSPS gene family expansion. The Ka/Ks ratio of pairwise MdSPS genes indicated that the members of this family have undergone strong purifying selection during domestication. Furthermore, three SPS gene subfamilies were classified based on phylogenetic relationships, and old gene duplications and significantly divergent evolutionary rates were observed among the SPS gene subfamilies. In addition, a major gene related to sucrose accumulation (MdSPSA2.3) was identified according to the highly consistent trends in the changes of its expression in four apple varieties (‘Golden Delicious’, ‘Fuji’, ‘Qinguan’ and ‘Honeycrisp’) and the correlation between gene expression and soluble sugar content during fruit development. Furthermore, the virus-induced silencing of MdSPSA2.3 confirmed its function in sucrose accumulation in apple fruit. The present study lays a theoretical foundation for better clarifying the biological functions of the MdSPS genes during apple fruit development.